Is website interactivity always beneficial? an elaboration likelihood model approach - Zotos, Yorgos; Palla, Polyxeni; Tsiotsou, Rodoula H. (My University, 2013)
In the evolving arena of mediated communication technology such as the Internet, interactivity becomes one of the most valuable features because it enables two-way or multiple communications. Interactivity distinguishes traditional media (TV, radio) from new or digital ones (Internet). Most importantly, it appears that interactive communication generates not only unprecedented behaviors but also new models of consumer behavior.
Keywords: Communication technology; Internet; Interactivity; Consumer behavior